Factors Affecting the Income of Line Fishermen in Batu Jaya Village, Laonti District, South Konawe Regency - Rahmad, Rahmad; Ine Fausayana; Wa Ode Yusria (International journal of technology and education research, 2025)
This research was carried out from January to March 2024, with the aim of 1) to determine the income of fishing fishermen in Batu Jaya Village, Laonti District, South Konawe Regency. 2) To find out what factors influence the income of fishing fishermen in Batu Jaya Village, Laonti District, South Konawe Regency. The method used in this research was carried out purposively and the sample was determined using a census method of 20 people. The analytical tools used are income analysis and multiple linear regression. The research results show that: 1) the average income of respondents is IDR 2,170,270 per month. 2) Find out the factors that influence the income of fishing fishermen